Search for dark matter with atlas : using events with a highly energetic jet and missing transverse momentum in proton-proton collisions = 8 TeV. /: using events with a highly energetic jet and missing transverse momentum in proton-proton collisions = 8 TeV. (2016) - Pöttgen, Ruth
No abstract available